Physiochemical and morphological responses of marigold (Tagetes erecta) genotypes under cold stress - AMALA, EDIGA; SINGH, K P; PANWAR, SAPNA; BANYAL, NAMITA; JAIN, NEELU; KUMAR, SUDHIR; T, VINUTHA; VERMA, PAVNESH KUMAR (The Indian Journal of Agricultural Sciences, 2022)
The objective of this study was to look into the physiochemical and morphological responses of marigoldgenotypes under cold stress, in order to identify the cold tolerant genotype. During the winter (rabi) season, 10genotypes of African marigold were grown in pots in open and polyhouse growing environments from December2020 to April 2021 at the research farm of ICAR-IARI, New Delhi. The results revealed that marigold genotypesshowed a severe drop in RWC, photosynthesis, transpiration, chlorophyll pigments and increased ELR and MDA content as the cold sensitive genotypes and vice versa was found in the Af./W-4 genotype. There was a significant decrease in the growth and yield parameters due to cold stress conditions in open as compared to polyhouse conditions. The genotypes Af./W-4 and Pusa Bahar recorded highest plant height and maximum plant spread, flower diameter, higher yield/plant respectively among all other African marigold genotypes. Therefore, genotypes Af/W-4 followed by Pusa Bahar are deemed the most tolerant under cold stress conditions, based on the basis of physiochemical and morphological responses.